Model-based approach for measurement of basic soil nutrient - Georgieva Tsvetelina; Penchev Stanislav; Paskova Nadezhda; Nedelcheva Eleonora; Daskalov Plamen (E3S Web of Conferences)
The article presents a model-based approach for measuring basic soil nutrients. The model-based approach consists of two main phases: data collection using sensor systems and data pre-processing and analysis. A microprocessor system has been developed for measuring basic physicochemical parameters of the soil. Based on the experimental results on the relationship between the main chemical elements and the main soil parameters, it was found that nitrogen strongly correlates with electrical conductivity (0.8304), phosphorus - significantly with acidity (0.5686), and potassium - moderately with acidity (0.3385). Models have been developed for the quantitative assessment of nitrogen, phosphorus and potassium through the measured values of soil acidity, electrical conductivity and moisture. The obtained results show that the developed models are of the 4th and 3rd order. For nitrogen and phosphorus, we could use one model with the values of the three physicochemical soil parameters with R2 0.996 and 0.989 respectively, but for potassium we have two models - EC (R2=0.979) and acidity and moisture (R2=0.994). Future research will be aimed at increasing the experimental data and testing the accuracy of the developed models.